Perineural Invasion and Histological Grades of Prostatic Adenocarcinoma - Ghazia Fatima, Zafar Iqbal,, Faiz Ahmad Faiz, Hira Ghaffar, Sibgha Naz, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: Perineural invasion and Histological grades of Prostatic adenocarcinoma Study design: Analytical descriptive cross sectional Study setting: Department of Pathology, KEMU, Lahore in collaboration with other tertiary care hospitals. Duration of study: 6 months Methodology: 60 cases of prostatic carcinoma were enrolled in this study. Detailed demographics of included patients were recorded after taking informed written consent. Formalin fixed, processed and paraffin embedded tissue blocks of prostate adenocarcinoma collected. Results: Out of 60 biopsies, 57(95%) were TURP, 1(1.67%) was a TRUS guided biopsy, 1(1.67%) was a core needle biopsy and 1(1.67%) was a radical prostatectomy specimen. Perineural invasion was identified in 27 cases. There was insignificant association between perineural invasion and histological grades of prostatic carcinoma and p-value = 0.613. Among all high grade tumors with Gleason score (8-10), 23 cases were positive for perineural invasion and 25 were negative. Conclusion: Perineural invasion was identified in 27 cases i.e. 45%. There was insignificant association between perineural invasion and histological grades of prostatic carcinoma. Key words: Prostate, adenocarcinoma, perineural invasion, association, TURP,